Soft wheat cultivars grown in the Saratov region and their resistance to Septoria blotch - Yu. V. Zeleneva; E. A. Konkova (Вавиловский журнал генетики и селекции)
Septoria is one of the harmful diseases of wheat cultivars cultivated in the Saratov region. This infectious disease of fungal etiology limits yield indicators and rapidly progresses in many regions of the Russian Federation. The aim of the research was to assess the resistance of winter and spring wheat cultivars that are referred to as promising and recommended for cultivation in the Low Volga region of the Russian Federation to pathogens of Septoria, to study the populations of Parastagonospora nodorum and P. pseudonodorum in the territory of the Saratov region in order to detect the presence of effector genes. Using molecular markers, we performed the identification of genes encoding NEs in 220 Parastagonospora spp. fungal isolates obtained from 7 cultivars of soft winter wheat, 6 taken from the winter triticale, 5 from soft spring wheat, 3 from durum spring wheat and 1 from spring oats. Among the P. nodorum isolates studied, there were both single genes Tox1, Tox3, and ToxA, and combinations of two genes in one genotype. The presence of the ToxA gene was not noted in the genotype of P. pseudonodorum isolates. During 2020–2022, a collection of winter and spring wheat cultivars was studied to detect resistance to Septoria blotch in field conditions (13 cultivars of winter wheat and 7 cultivars of spring wheat accordingly). The resistance of the cultivars was proven by laboratory evaluation. Three inoculums were used, including the isolates of Z. tritici, P. nodorum (ToxA, Tox1, Tox3), P. pseudonodorum (ToxA, Tox1, Tox3) mainly obtained from Saratov populations of 2022 (except for P. pseudonodorum with the ToxA gene). The tested cultivars were characterized using the Xfcp623 molecular marker, diagnostic for Tsn1/ tsn1 genes, which controls sensitivity to the fungal toxin of PtrToxA. Of greatest interest are 11 wheat genotypes that showed resistance to one, two and three species which served as causative agents of Septoria blotch (Zymoseptoria tritici, P. nodorum, P. pseudonodorum). These are the soft winter wheat cultivars Gostianum 237 (tsn1), Lutescens 230 (Tsn1), Guberniya (Tsn1), Podruga (Tsn1), Anastasia (Tsn1), Sosedka (Tsn1) and the soft spring wheat cultivars Favorit (tsn1), Prokhorovka (tsn1), Saratovskaya 70 (tsn1), Saratovskaya 73 (tsn1), Belyanka (tsn1). The results obtained are of interest as they might increase the efficiency of selection based on the elimination of genotypes with dominant Tsn1 alleles sensitive to PtrToxA. In addition to the economic value of the cultivars studied, it is recommended to use them in breeding for resistance to Septoria blotch.